A Politeness and Expressive Acts in Diplomatic Discourse: A pragmatic Analysis of Marape’s 2024 Address to the Australian Parliament - Stephanie Yakumbu; Riki Nasrullah; Ina Ika Pratita (UIN Salatiga, 2025)
This study examines the pragmatic strategies of politeness and expressive acts in Prime Minister James Marape’s historic 2024 address to the Australian Parliament. It focuses on how language is used to perform diplomacy, assert postcolonial identity, and reaffirm regional presence. The research aims to explore how speech acts particularly those expressing gratitude, acknowledgment, and storytelling serve not only interpersonal but also symbolic and ideological functions in high-level diplomatic discourse. Employing a qualitative descriptive approach, the study is grounded in Brown and Levinson’s politeness theory and informed by postcolonial pragmatics. Selected excerpts from the speech were analyzed for their pragmatic density and thematic relevance. The findings show that Marape employs positive politeness to foster solidarity and shared authority, negative politeness to express humility while affirming legitimacy, and off-record strategies especially narrative storytelling to reclaim historical voice. Expressive acts such as environmental imagery and geographic reframing reinforce Papua New Guinea’s national identity and geopolitical stance while maintaining diplomatic decorum. The analysis reveals that politeness in postcolonial diplomatic settings functions as a complex communicative strategy that negotiates power, history, and cultural dignity. This study contributes to the expanding field of postcolonial pragmatics by offering a Pacific perspective and illustrating how diplomatic speeches can serve as performative acts of historical redress and regional engagement.